PENTINGNYA PENGELOLAAN KEUANGAN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM): Analisis Tahapan Pengelolaan Keuangan sebagai Kerangka Dasar Manajemen UMKM - Sumarjono; Amin Wardjo; Saiman; Sudarman; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia's economy, contributing about 60% to the Gross Domestic Product (GDP) and absorbing a large workforce. MSMEs also improve community welfare and drive innovation (Ministry of Cooperatives and SMEs, 2022). MSMEs face challenges in financial management because their owners do not manage finances well according to applicable accounting standards (Hartina et al., 2023). Many MSME actors do not yet understand the importance of structured financial recording, budget planning, cash flow management, and financial reporting. This causes difficulties in business decision-making and access to formal financing. Therefore, this study was conducted to analyze how financial management is applied by MSME actors, the supporting factors and obstacles, and its impact on business performance. This study uses a library research method, which is research done by reviewing, studying, and analyzing various literature sources relevant to the discussed topic. The basic aim of financial management is to realize the predetermined goals. Thus, knowledge of asset structure, finance, and capital can be obtained from practice. Furthermore, to achieve this, a manager must follow the principles of consistency, accountability, transparency, business or personal continuity. In this financial management, the manager has an integrated plan that minimizes risks as much as possible.